(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
In order to provide the basic data for the development of medical guide-wire and a simulator for the PTCA (Percutaneous Transluminal Coronary Angioplasty), we have developed the blood vessel model made of PVA hydrogel and investigated the mechanical characteristics of guide-wire in the blood vessel model. In the present study, we discussed the characteristics of torque transmission and rotational response of the guide-wire in curved blood vessel model with change in the PVA concentration of the hydrogel and thickness of blood vessel model.